Ovarian Reserve and Serum Concentration of Thyroid Peroxidase Antibodies in Euthyroid Women With Different Polycystic Ovary Syndrome Phenotypes - Adamska, Agnieszka; Łebkowska, Agnieszka; Krentowska, Anna; Hryniewicka, Justyna; Adamski, Marcin; Leśniewska, Monika; Polak, Aleksandra Maria; Kowalska, Irina (Frontiers in Endocrinology, 2020)
Objective: It has been shown that women with polycystic ovary syndrome (PCOS), as well as with Hashimoto’s thyroiditis (HT), are characterized by increased incidence of infertility. Serum anti-Müllerian hormone (AMH), which reflects ovarian reserve, is elevated in PCOS women and is decreased in women with HT. The Rotterdam criteria recognize four clinical PCOS phenotypes, i.e., phenotype A, B, C and D. The aim of the present study was to investigate the relation between serum concentrations of thyroid peroxidase antibodies (TPOAbs) and ovarian reserve in different PCOS phenotypes. Patients and methods: We examined 141 women with PCOS (phenotype A was diagnosed in 67 (47.5%) women, phenotype B in 30 (21.3%), phenotype C in 28 (19.9%), phenotype D in 16 (11.3%)) and 88 control subjects of similar age, all women were euthyroid. Serum concentration of AMH, TSH, thyroid hormones and TPOAbs were assessed. Results: We observed positive serum TPOAbs in 21.9% women with PCOS and in 23.9% controls (p=0.07). We did not find differences in the frequency of detection of positive serum TPOAbs between phenotype A, B, C and the control group (p>0.05). We did not observe a difference in AMH levels between TPOAbs-positive and TPOAbs-negative women, both in the control group and PCOS women (all p>0.05). However, serum AMH concentration was markedly higher in the whole PCOS group (p<0.01) and in phenotype A (p<0.01) vs. controls when serum concentration of TPOAbs was negative. In the groups with positive serum levels of TPOAbs, serum concentration of AMH did not differ between PCOS phenotypes and controls (p=0.23). Additionally, we observed that serum AMH concentration was related to the level of TPOAbs in the PCOS group (r=-0.4, p=0.02). Conclusions: The frequency of serum detection of positive TPOAbs did not differ between PCOS phenotypes with clinical/biochemical hyperandrogenism and the control group. The observation of the difference in serum AMH between PCOS and control group only in TPOAbs negative women together with inverse relation of TPOAbs with serum AMH only in PCOS group might suggest that ovarian reserve is influenced by TPOAbs in PCOS.